Comparative Senses-based Investigation of Traditional and Modern Apple Cultivars - Dremák, Péter (Acta Agraria Debreceniensis, 2004)
Apple consumption has significantly decreased over the last 10-15 years in Hungary. While consumption of fresh apple was 25 kg/person/year before the change of regime, today it hardly exceeds 10 kg according to careful estimations. In spite of the fact that the former dull cultivar structure (Jonathan, Starking, Golden Delicious) has widened with numerous new cultivars, apple consumption in Hungary has not increased. Unfortunately, customers do not or scarcely know most of these new cultivars. In a survey conducted among the students of five Hungarian universities, we gathered information about comsumer opinion of both and older cultivars. Numerous questonnaires – 592 – were filled out on 8 cultivars (Jonagold, Novajo, Topaz, Golden Reinders, Idared, Pinova, Braeburn, Jonathan, Starking) about the qualitiy parameters that determine the value for consumption. The results clearly show that besides the old cultivars, such cultivars are preferred that are known worldwide, such as Jonagold, or Golden (free of russetting) or the resistant Topaz. Promotion of these cultivars and creating the possibility of their supply can help to increase a fresh apple consumption.